(untitled) (Praxis Educativa, 2025)
The following paper analyzes, from a socio-historical approach with an emphasis on the social history of knowledge and experts through a gender perspective, the Ninth Congress of the International Association for Physical Education and Sport for Girls and Women, held in Buenos Aires in 1981. It explores, in a particular socio-political context, three dimensions of this significant academic event: the circulation of knowledge; the emergence of certain women experts in validating specific political-pedagogical interventions; and the promotion of certain institutions. Among the conclusions, we identify four narratives on how to think about female physical education by certain women experts. However, at the same time, the congress did not question institutional violence, state terrorism, or the violation of human rights that were publicly known in Argentina during the civic-military dictatorship. That is to say, during the international congress, certain forms of violence were visibilized and denounced, while others were deliberately omitted and invisibilized.